2012
DOI: 10.1111/j.1528-1167.2012.03493.x
|View full text |Cite
|
Sign up to set email alerts
|

Detecting epilepsy‐related cognitive problems in clinically referred children with epilepsy: Is the WISC‐IV a useful tool?

Abstract: Summary Purpose:  The Wechsler Intelligence Scale for Children – Fourth Edition is the most widely used intelligence quotient (IQ) test in use today. However, despite numerous studies on IQ in childhood epilepsy, data exist almost exclusively from prior editions of the test, and no studies to date provide information on the sensitivity of specific WISC‐IV scores (full‐scale IQ [FSIQ], index, and subtest scores) to epilepsy‐related cognitive impairments. The goal of this study was to determine the relative sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 15 publications
5
56
1
2
Order By: Relevance
“…Symbol Search is a subtest measuring processing speed and visual attention, suggesting that the primary difficulty for children relates to complex attention and working memory and not to motor speed [29]. Matrix reasoning is a subtest of the PRI; therefore, our results suggest a deficit in reasoning and abstraction in the verbal and visual modalities of children with complex FS.…”
Section: Wisc-iv Performancementioning
confidence: 66%
See 1 more Smart Citation
“…Symbol Search is a subtest measuring processing speed and visual attention, suggesting that the primary difficulty for children relates to complex attention and working memory and not to motor speed [29]. Matrix reasoning is a subtest of the PRI; therefore, our results suggest a deficit in reasoning and abstraction in the verbal and visual modalities of children with complex FS.…”
Section: Wisc-iv Performancementioning
confidence: 66%
“…Difficulties in Processing Speed and Working Memory were the most prominent in Table 4 Event-related potential (ERP) latencies (msec) in controls and in groups with different types of febrile seizures. children with epilepsy [29]. Long-term psychological studies have documented that the chronic effect on declarative memory systems in patients with epilepsy and cumulative cognitive impairment increase with the duration of seizures [32][33][34].…”
Section: Wisc-iv Performancementioning
confidence: 99%
“…It is well established that those with ADHD-I may show slow response speeds (Diamond, 2005), and it has been shown that ''sluggish cognitive temp'' is strongly related to the DSM-IV constructs of inattention (Hartman, Willcutt, Rhee, & Pennington, 2004). It is perhaps then not surprising that those with epilepsy and ADHD-I would show even slower response speeds, given the fact that processing-speed deficits are common in epilepsy (Dow, Seidenberg, & Hermann, 2004;Pascalicchio et al, 2007;Sherman, Brooks, Fay-McClymont, & MacAllister, 2012). Moreover, many AEDs have cognitive slowing as a side effect (Loring & Meador, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…For example, age of epilepsy onset is a robust predictor of overall cognitive dysfunction across numerous studies (Berg et al, 2008;Farwell et al, 1985;O'Leary et al, 1983;Schoenfeld et al, 1999;Sherman, Brooks, Fay-McClymont, & Macallister, 2012). Likewise, high seizure frequency (Bourgeois, Prensky, Palkes, Talent, & Busch, 1983;Farwell et al, 1985;Sherman et al, 2012), multiple seizure types (e.g., generalized seizures [generalized tonic-clonic seizures, absence seizures], partial-complex seizures), and the need for more than one antiepileptic drug (Bourgeois et al, 1983;Bulteau et al, 2000;Sherman et al, 2012) have been associated with greater cognitive dysfunction. It is also important to recognize that specific antiepileptic medications have more or less favorable side-effect profiles and may adversely impact cognition (Loring, Marino, & Meador, 2007;Loring & Meador, 2004;).…”
Section: General Cognition In Children With Epilepsymentioning
confidence: 99%